The Influence of Product Quality and Cafe Service Quality on Consumers' Repurchase Interest in Cafe Janji Mantan in Lahat - Afiqa Alifia Anyenlita; Hayani Hayani; Iskandar Iskandar (Universitas Dehasen Bengkulu, 2026)
This study aims to determine how product quality and service quality partially and simultaneously influence consumer repurchase intention at Cafe Janji Mantan in Lahat. The sample size for this study was 66 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS software, resulting in a regression equation . The results showed a significant effect between marketing strategy and consumer repurchase intention at Cafe Janji Mantan in Lahat. Service quality also significantly influenced consumer repurchase intention at Cafe Janji Mantan in Lahat. The F-test showed that product quality and service quality simultaneously influenced consumer repurchase intention at Cafe Janji Mantan in Lahat.